The Students' Perceptions of Practicing Speaking Skill By Using British Council Website - Ali, Aprilia Anggraini; Palupi, Ica Catur; Aini, Nurul (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2023)
This study aims to determine the perception of the use of the British Council website. This study uses quantitative methods and the research participants were 20 students in the 6th semester of the English Education Program at IAIN KEDIRI with twenty one statements concerning how they felt about using British Council Website to practice their English language skills. The data were collected through a questionnaire distributed to students using Google Forms. The highest point of those questionnaires was students “Agree” that British Council Website helps them practice in speaking. While the lowest point of questionnaires was “Disagree”. They can improve their speaking skill by noting important details in their notebook when they watch videos on the British Council Website. In addition, the finding shows that British Council website is effective to help teacher in delivering material and boosting the students’ motivation to speak. In conclusion, many students agree that the British Council website can help students with their problems in learning English.